Determinant and conditioning factors of feline asthma: a questionnaire-base study - RODRIGUES, j.; CAROLINO, N.; NUNESD, f.; DUARTE, S. C. (Journal of the Hellenic Veterinary Medical Society, 2021)
Feline asthma is a chronic inflammatory disease of the lower respiratory airways that has shown an increased incidence in the past decades, aside with human asthma. It is also important to acknowledge that human and feline asthma are very similar in their pathophysiology,being the housing conditions (pollutants, stress and obesity) major risk factors to its development. The present study aimed to investigate if these housing conditions could be determining and conditioning factors associated with the occurrence of feline asthma previously reported in literature. A cross-sectional (self-completed) questionnaire-based study targeting Portuguese-speaking owners of cats was carried out, validated and applied (in both paper and digital form) between September 2018 and March 2019. A total of 189 questionnaires were analysed, of which 18 corresponded to cats with respiratory disease. Most of studied cats were of mixed breed and neutered, living indoor exclusively, mainly in urbanareas and from the north mainland region. According to the owner’s perception, the cats were mostly active and with the ideal weight. The clinical signs more often associated with asthma crisis were respiratory wheezes and cough, whereas the worsening of such clinical signs occurred mostly in spring. Stress symptoms were not common, but the correlation between stress-related diseases and asthma was close to significance (P=0.065). A mixed lifestyle was associated with less symptoms of stress (P=0.032). Although close to significance (P=0.07), the presence of pollutant industries was not associated to asthma in the enrolled cats. Finally, in most of the houses in which an asthmatic cat lived in, no owner or other co-inhabitant had asthma. The paucity of similar epidemiological studies in cats demonstrates the importance of the current work and the need to conduct further studies on housing conditions associated with the disease. Eventually, further studies will clarify if cats could be used as sentinels for human asthma.